The middle class in neo-urban India: Space, class and distinction - Singh, Smriti (London Routledge, 2024)
Class identity, vulnerability and hierarchy influence the actions and motivations of the middle class. The author studies the nuances and socio-political fractures stemming from the complex dynamic of class, caste, religion and gender that manifest in these neo-urban spaces and how these shape the city and community.
Keywords: Sociology; Political sociology; Urban sociology